Chemisorbed oxygen or surface oxides steer the selectivity in Pd electrocatalytic propene oxidation observed by operando Pd L-edge X-ray absorption spectroscopy. Issue 10 (1st March 2021) - Koroidov, Sergey; Winiwarter, Anna; Diaz-Morales, Oscar; Görlin, Mikaela; Halldin Stenlid, Joakim; Wang, Hsin-Yi; Börner, Mia; Goodwin, Christopher Matthew; Soldemo, Markus; Pettersson, Lars Gunnar Moody; Rossmeisl, Jan; Hansson, Tony; et al.
Abstract : Operando Pd X-ray absorption spectroscopy elucidates how the surface oxygen species steer the selectivity in the electrochemical oxidation of propene. Abstract : Controlled electrochemical oxidation of hydrocarbons to desired products is an attractive approach in catalysis. Here we study the electrochemical propene oxidation under operando conditions using Pd L-edge X-ray absorption spectroscopy (XAS) as a sensitive probe to elucidate surface processes occurring during catalysis. Together with ab initio multiple-scattering calculations, our XAS results enable assignment of characteristic changes of the Pd L-edge intensity and energy position in terms of a mechanistic understanding of the selective oxidation of propene. The results, supported by electrochemical density functional theory DFT simulations, show that in the potential range of 0.8–1.0 V vs. the reversible hydrogen electrode (RHE), selective oxidation of propene to acrolein and acrylic acid occurs on the metallic Pd surface. These reactions are proposed to proceed via the Langmuir–Hinshelwood mechanism. In contrast, for the potential range of 1.1–1.3 V vs. RHE, selective oxidation of propene to propylene glycol takes place on a Pd oxide surface.